1992
DOI: 10.1097/00000658-199212000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Types I and III Propeptides as Markers of Healing in Chronic Leg Ulcers A Noninvasive Method for the Determination of Procollagen Propeptides in Wound Fluid—Influence of Growth Hormone

Abstract: A noninvasive method allowing measurements of the propeptides of collagen type III (PIIINP) and type I (PICP) in ulcer washings was developed. The response to topical human growth hormone was examined. Fourteen patients with venous ulcers were treated sequentially with human growth hormone (0.1, 0.25, and 1 IU/cm2/day), each dose for 1 week, followed by 1 week washout. On alternate days, three and two times during treatment and washout periods, respectively, the ulcers were washed and incubated for 30 minutes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…It is not only a major constituent of normal synovial membrane,23 but also present in inflamed24 and proliferative rheumatoid synovial membrane 25. Further, it is synthesized during wound healing26 and replaced by collagen type I 27. The determination of collagen types I and III expression levels is of value in assessing whether the changes in the capsule of a joint developing a contracture are of a proliferative/secretive or a degenerative/ catabolic nature 18…”
mentioning
confidence: 99%
“…It is not only a major constituent of normal synovial membrane,23 but also present in inflamed24 and proliferative rheumatoid synovial membrane 25. Further, it is synthesized during wound healing26 and replaced by collagen type I 27. The determination of collagen types I and III expression levels is of value in assessing whether the changes in the capsule of a joint developing a contracture are of a proliferative/secretive or a degenerative/ catabolic nature 18…”
mentioning
confidence: 99%
“…These proteases may also be regarded as markers of inflammatory and connective tissue cell activity, respectively 11,12 . On the synthetic side, it has been shown that levels of the propeptide markers of collagen synthesis are modulated during healing 13‐15 . All of these components may be collected noninvasively from wound exudates.…”
mentioning
confidence: 99%
“…This trend was also demonstrated by collagen III immunohistochemical analysis, although collagen I results showed an increase from day 0 to day 14. Collagen I and III were chosen as the most appropriate markers as both of these types of collagens are formed in large quantities in granulation tissue in the healing wound . Previous studies had reported rapid collagen accumulation during the first 3 weeks of healing .…”
Section: Discussionmentioning
confidence: 99%